DETERMINING THE QUALITY OF EDUCATORS AND TEACHER WORK PRODUCTIVITY: COMPETENCY AND SOFT SKILL ANALYSIS - Junaidi JM; Kemas Imron Rosadi (Dinasti International Journal of Education Management And Social Science, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the Determination of the Quality of Educators and Teacher Work Productivity: Competence and Soft Skill Analysis, A Study of Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this research library are that: 1) Competence affects the Quality of Educators; 2) Soft Skills affect the Quality of Educators; 3) Competence has an effect on Teacher's Work Productivity; 4) Soft Skill has an effect on Teacher's Work Productivity; and 5) Quality of Educators has an effect on Teacher Work Productivity.